1994
DOI: 10.1002/jcp.1041600214
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ alters growth and differentiation related gene expression in proliferating osteoblasts in vitro, preventing development of the mature bone phenotype

Abstract: This study examines the mechanism by which TGF-beta 1, an important mediator of cell growth and differentiation, blocks the differentiation of normal rat diploid fetal osteoblasts in vitro. We have established that the inability for pre-osteoblasts to differentiate is associated with changes in the expression of cell growth, matrix forming, and bone related genes. These include histone, jun B, c-fos, collagen, fibronectin, osteocalcin, alkaline phosphatase, and osteopontin. Morphologically, the TGF-beta 1-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
82
1
8

Year Published

1995
1995
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 69 publications
8
82
1
8
Order By: Relevance
“…This pattern, similar to AP activity, may be the response of PLA cell subpopulations at distinct developmental stages to osteogenic induction. In support of this, several other induction agents have been shown to stage-specific effects on osteogenesis, including TGF␤ (Breen et al, 1994). Finally, OC expression by induced PLA cells was dependent upon osteogenic agent as OC expression was inhibited upon dexamethasone exposure, an effect not observed in MSC controls.…”
Section: Osteogenesismentioning
confidence: 74%
“…This pattern, similar to AP activity, may be the response of PLA cell subpopulations at distinct developmental stages to osteogenic induction. In support of this, several other induction agents have been shown to stage-specific effects on osteogenesis, including TGF␤ (Breen et al, 1994). Finally, OC expression by induced PLA cells was dependent upon osteogenic agent as OC expression was inhibited upon dexamethasone exposure, an effect not observed in MSC controls.…”
Section: Osteogenesismentioning
confidence: 74%
“…The resulting dimers can bind to DNA at a consensus AP1 binding site termed the TPA response element (TRE), thereby transactivating the expression of AP1-responsive genes (St-Arnaud and Quelo, 1998). Experiments where fos and jun expression in the bone was modulated by steroid hormone treatment or by overexpression or ablation of fos or jun genes suggest that the Fos and Jun proteins are important in the regulation of bone formation (Clohisy et al, 1992;Breen et al, 1994). This suggestion is supported by a study by McCabe et al (1996), who showed that the developmental expression and activity of particular Fos and Jun proteins are functionally related to osteoblast maturation.…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming clear that the TGF-fl supergene family plays an instrumental role for the osteoblastic cell lineage to display its full catalogue of phenotypic characteristics during osteogenesis. In various experimental systems for studying bone formation, contradictory results have been obtained on whether TGF-fll enhances or inhibits bone matrix formation, mineralization and the expression of bone marker proteins [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. This has in part been explained by differences in the source and type of cells, stage of osteoblastic maturation, culture conditions and presence of other cytokines and their receptors.…”
Section: K Iba Et Al/febs Letters 373 (1995) 1~1mentioning
confidence: 99%
“…Based on all these in vitro and in vivo studies, several authors suggested that, while TGF-fll initiates the proliferation, differentiation and extracellular matrix synthesis of bone cells, TGF-fll may be less involved in or actually inhibit the later phases of osteogenesis, i.e. mineralization [17,20,21]. The biological responses to TGF-fl may be mediated by the retinoblastoma gene product [38], which binds to the SV-40 T antigen, and therefore the effect of T antigen expression by the SV-HFO cells on the TGF-fll signal transduction pathway will require further analysis.…”
Section: K Iba Et Al/febs Letters 373 (1995) 1~1mentioning
confidence: 99%
See 1 more Smart Citation